1983
DOI: 10.1037/0096-3445.112.3.413
|View full text |Cite
|
Sign up to set email alerts
|

Relating age at encoding in early childhood to adult recall: Development of flashbulb memories.

Abstract: Three hundred thirty-eight informants who were between 1 and 7 years of age in 1963 were asked about their personal memories surrounding the assassination of President Kennedy and six other significant public events. The probability and degree of elaboration of recall showed a gradual growth function with increasing age at the time of the event for the assassinations of John F. Kennedy and Robert F. Kennedy but not for the other events. Self-reports of amount of rehearsal showed a low correlation with recall. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
100
1
5

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(114 citation statements)
references
References 20 publications
8
100
1
5
Order By: Relevance
“…For the WWII population in Study 1, a similar pattern was observed for the presence and vividness of participants' personal memories of the day of the German invasion and the day of their capitulation, (though vividness also correlated weakly with age after age 7). The findings related to memories for the two historical events agree with studies of childhood amnesia generally (e.g., Nelson, 1993;Rubin, 2000;Pillemer & White, 1989;Usher & Neisser, 1993) and more specifically with previous studies on age differences in the development of flashbulb memories (Berntsen & Thomsen, 2005;Teckan & Pernircio lu, 2002;Winograd & Killinger, 1983). The fact that the relation between longterm posttraumatic stress reactions and age at the time of the event mirrors the age-related ability of retaining autobiographical memories from childhood to adulthood has at least two possible interpretations: One possibility is that posttraumatic stress reactions (in terms of reexperiencing, avoidance and hyperarousal, American Psychiatric Association, 1994) depend on the presence of autobiographical memory abilities.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…For the WWII population in Study 1, a similar pattern was observed for the presence and vividness of participants' personal memories of the day of the German invasion and the day of their capitulation, (though vividness also correlated weakly with age after age 7). The findings related to memories for the two historical events agree with studies of childhood amnesia generally (e.g., Nelson, 1993;Rubin, 2000;Pillemer & White, 1989;Usher & Neisser, 1993) and more specifically with previous studies on age differences in the development of flashbulb memories (Berntsen & Thomsen, 2005;Teckan & Pernircio lu, 2002;Winograd & Killinger, 1983). The fact that the relation between longterm posttraumatic stress reactions and age at the time of the event mirrors the age-related ability of retaining autobiographical memories from childhood to adulthood has at least two possible interpretations: One possibility is that posttraumatic stress reactions (in terms of reexperiencing, avoidance and hyperarousal, American Psychiatric Association, 1994) depend on the presence of autobiographical memory abilities.…”
Section: Discussionsupporting
confidence: 90%
“…These two events seem especially appropriate for this type of analysis, since Berntsen and Thomsen (2005) found that among Danes who were at least nine years old at the time of the invasion, virtually everybody reported a memory for these two events. Here we extend Winograd and Killinger's (1983) study in four ways. First, by using samples of older Danes who were between 0 and 26 years old at the time of the invasion and between 0 and 31 years old at the liberation, we are able to analyze memory as a function of age, using a larger agespan than the 1-7 years span used by Winograd and Killinger for the assassination of President Kennedy.…”
Section: Flashbulb Memoriesmentioning
confidence: 95%
See 1 more Smart Citation
“…Apparently, memory researchers have found it easier to find highly surprising public events with a negative, rather than a positive, content. Also, Brewer's (1992) review of the role of surprise in the formation of flashbulb memories suggests, together with more recent work, that flashbulb memories for positive events often occur with low levels of surprise (e.g., Berntsen & Thomsen, 2005;Winograd & Killinger, 1983), whereas studies that have shown surprise as essential have been studies involving negative events (e.g., Christianson, 1989;Er, 2003;Finkenauer et al, 1998). Thus, mechanisms that are assumed to be crucial for the formation of flashbulb memories can be seen to interact with whether the target event is emotionally positive or negative.…”
mentioning
confidence: 99%
“…On the one hand, memory for trauma is viewed as fixed or indelible, remaining remarkably accurate over the lifetime of the individual (1)(2)(3)(4). On the other hand, it is seen as malleable and subject to substantial distortion and alteration (5)(6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%